The Down-Regulation of SUZ12 Accelerates the Migration and Invasion of Liver Cancer Cells via Activating ERK1/2 Pathway - Xue, Cailin (J Cancer, 2019)
The suppressor of zest 12 (SUZ12), an essential subunit of the transcription polycomb repressive complex 2 (PRC2), has been found to be involved in HBV X-induced oncogenic transformation in hepatocellular carcinoma (HCC). However, the specific function of SUZ12 has not yet been determined in the pathogenesis of migration and invasion of HBV-associated HCC. Here, our results showed that SUZ12 was significantly down-regulated in HBV-related HCC tissues compared with adjacent non-tumor tissues by immunohistochemical and Western blot assays. The 5-years survival rate was worse in patients with low expression level of SUZ12. SUZ12 silencing increased the migration and invasion of HCC cells, and its overexpression impaired HCC cells migration and invasion. Knockdown of SUZ12 activated ERK1/2 pathway and increased MMP9 (matrix metallopeptidase 9) and MMP2 (matrix metallopeptidase 2) expression, whereas SUZ12 overexpression had opposite effects. Specific ERK1/2 inhibitor (SCH772984) significantly decreased HCC cells migration and invasion caused by SUZ12 shRNA. Thus, the liver cancer-down-regulated SUZ12 accelerated the invasion and metastasis of HCC cells. These effects might be associated with deregulation of SUZ12 activating ERK1/2, MMP2 and MMP9 in HCC cells.